RESEARCH ON NUMERICAL SIMULATION METHOD OF THREAD CONNECTION BASED ON FINITE ELEMENT METHOD - JI FangFang; WANG YuBin; LIU Xia (Jixie qiangdu)
A method of forced angular displacement loading based on ABAQUS software is proposed. In order to improve the efficiency of pretreatment, the type of model elements is selected as C3 D8 R and C3 D10 M suitable for contact analysis according to the structural characteristics of the threaded joints. In this method, the mechanical constraint is treated by balanced penalty function. The boundary conditions are established at the bolt head according to the way of obtaining the pretightening force in engineering. The pretightening force is defined by imposing a forced angular displacement on the rigid element. This method is simpler and more practical than other methods. Finally, the relationship between pretightening force and torsion is obtained by analyzing the thread connection structure of skirt plate lock with this method. The error between the results and the experimental results is within 8%, which is within the range of theoretical calculation. The validity of this method is proved.